Casa de mulher: os circuitos cotidianos de cuidado, dinheiro e violência em São Carlos/SP - Pinho, Isabela Vianna (2019)
This dissertation shows us how state, gender, economy, kinship and family are produced and connected in everyday life. Here, I analyze the forms that Maria, Bela, Ana and Rosa dwell to ordinary life. Residents of a neighborhood promoted by the federal program Minha Casa, Minha Vida in São Carlos/SP, the four women are also (or were) holders of the Bolsa Família program. Research shows that the two politics are one among other possible universes of meaning by which they move. The text is divided into two parts. In the first, I argue that the processes of life and of houses, as well as the ways of living and houses, are entangled in everyday life; also show how the past are embedded in the present and extraordinary events are embedded in the ordinary. In a second moment, I argue that the house can only be thought of in configuration, that is, it only exists in relation. Thus, in the last chapters I describe three everyday circuits - of care, money and violence - that mutually shape the configuration of houses. By looking at such circuits, it is possible to analyze the flows of objects and people as well as the relationships of violence and conflict within and between houses. In addition, the circuits demonstrate that there is an intersection between supposed antinomies such as money and intimacy; economic domain and affection; life and economy; home and work; reproduction and production. As a methodological and analytical strategy, I argue that an ethnography of 'woman's house' in configuration allows one to see the 'between'; that is, it makes it possible to capture sociological phenomenon relationally. What will be seen here will be lines that expose the offal put into practice by Maria, Bela, Ana and Rosa to make the world habitable again with each new event.